2002
DOI: 10.1046/j.1439-0264.2002.00355.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dimecron on Developing Chick Embryo: Malformations and other Histopathological Changes

Abstract: The effect of dimecron, an organophosphorus insecticide, on developmental alterations and histopathological damage was determined in the developing chick embryo. The insecticide was administered at two different doses (25 microg and 35 microg) into the egg yolk through a pore into the equatorial region at day 0 of incubation. Significant abnormalities in relation to organogenesis and overall retardation in growth were noted in the insecticide-treated embryos. Histopathological study of the treated whole embryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
1
3
1
Order By: Relevance
“…Manner et al (2003) observed that only 50% of suramin treated embryos survived until embryonic day 8 when exposed on embryonic day 3 as compared with control embryos. However in contrast to our results, dose-dependent increase in embryolethality was observed by Verrett et al (1969), Korhonen, Hemminki, and Vainio (1983), Kumar and Devi (1992), Zhao et al (1997), Pourmirza (2000), Sahu and Ghatak (2002), Rachid, Houria, and Reda (2008), Wagh, Deshpande, and Salokhe (2011), and Mobarak and Al-Asmari (2011) in chick embryo exposed to various xenobiotics. It is difficult to compare the presently estimated mortality result in chick embryo with that of chronic toxic study conducted by El-Kashoury et al (2009) because they reported only 25% and 30% mortality rate in male rate exposed to 30 ppm and 120 ppm of Kelthane (different commercial formulation of dicofol), respectively.…”
Section: Teratological Changescontrasting
confidence: 99%
See 1 more Smart Citation
“…Manner et al (2003) observed that only 50% of suramin treated embryos survived until embryonic day 8 when exposed on embryonic day 3 as compared with control embryos. However in contrast to our results, dose-dependent increase in embryolethality was observed by Verrett et al (1969), Korhonen, Hemminki, and Vainio (1983), Kumar and Devi (1992), Zhao et al (1997), Pourmirza (2000), Sahu and Ghatak (2002), Rachid, Houria, and Reda (2008), Wagh, Deshpande, and Salokhe (2011), and Mobarak and Al-Asmari (2011) in chick embryo exposed to various xenobiotics. It is difficult to compare the presently estimated mortality result in chick embryo with that of chronic toxic study conducted by El-Kashoury et al (2009) because they reported only 25% and 30% mortality rate in male rate exposed to 30 ppm and 120 ppm of Kelthane (different commercial formulation of dicofol), respectively.…”
Section: Teratological Changescontrasting
confidence: 99%
“…Furthermore, Kumar and Devi (1992) reported teratological abnormalities such as short neck, abdominal hernias, and hemorrhagic spots in brain and upper body which were predominant in 20-day-old chick embryos exposed to methyl parathion on embryonic days 4 and 6. The majority of malformations are in agreement with previous studies in developing chick embryos with captan and related compounds (Verrett et al 1969), 2,2 0 ,4,4 0 ,5,5 0 -hexachlorobiphenyl (Zhao et al 1997), dimecron (Sahu and Ghatak 2002), suramin (Manner et al 2003), chlorpyrifos and cypermethrin (Uggini, Patel, and Balakrishnan 2012), hexavalent chromium (Asmatullah and Shakoori 1998), bendiocarb (Petrovova et al 2010), lufenuron (Wagh, Deshpande, and Salokhe 2011), and methylmercury (Heinz et al 2011). Growth retardation effect of pesticide (dicofol) on the developing chick could be due to its inhibitory effect/disturbance on metabolism or after disruption of the retinoid signaling pathway in cells, which play an essential role in the proliferation, development, and differentiation of cells and disruption that can lead to malformation or abnormal development of eye, brain, heart, and limbs during the ''critical'' growing phase (Mobarak and Al-Asmari 2011).…”
Section: Teratological Changessupporting
confidence: 91%
“…Feeding habits of birds seem to take on an important role in the occurrence of pesticides in their eggs (Fasola et al, 1987). The presence of pesticides in the developing avian egg has been shown to result in decreased hatchability (Indyk, 1999), increased mortality (Pourmirza, 2000) and various congenital anomalies (Sahu and Ghatak, 2002). Accordingly, we aimed in this study to investigate the extent of edible egg contamination with different pesticide residues in our area, and to establish whether relative differences in these pesticide residue concentrations occurred within the different forms (farm and home produced) of egg production or not, taking in considerations the level of human exposure to these contaminants through consumption of eggs from both types that were chosen.…”
Section: Ne Usmentioning
confidence: 99%
“…Although a link between use of pesticides and amphibian population decline has not yet been established, there is experimental evidence demonstrating that exposure to pesticides may be harmful to embryo development (Lien et al, 1997;Harris et al, 1998;Gillilland et al, 2001;Karen et al, 2001;Sahu and Ghatak, 2002).…”
Section: Introductionmentioning
confidence: 99%